The influence of social support, physical activity, general psychological distress, and demographic characteristics on self-reported health status among women in Iran - Badriyeh Karami; Shahab Rezaeian; Ebrahim Shakiba; Amirhossien Naghibzadeh; Abbas Mohammad Karimi Mazhin; Masoumeh Malek; Hadi Darvishigilan (PLoS ONE, 2026)
Background Considering the impact of social support on women’s mental health and the importance of their mental health in improving the health of the society, this study aimed to investigate the influence of social support, physical activity, general psychological distress, and demographic characteristics on self-reported health status among women. Methods This cross-sectional study was conducted on 350 women aged 18–75 in 2024 in Iran. The Vaux social support, international physical activities, Depression- Anxiety- Stress Scale (DASS-21) questionnaires were administered. The Cluster random sampling method was used. The data were analyzed using STATA version 18. The significance level for examining the hypotheses was p ≥ 0.05. Results According to the results, there was a significant positive relationship between age, place of residence, history of chronic disease, evaluation of financial status and self-rated health in both crude and adjusted models. In addition, the positive significant relationship was observed between general psychological distress, and poor self- rated health in adjusted model. So that, the odds of poor self- rated health in women who achieved higher depression, anxiety, stress scale score was 1.04 times higher than others. Conclusion Considering the rising rates of psychological problems, particularly in recent years among women, as well as the influence of women’s health on societal well-being, it is imperative for policymakers in women’s health to pinpoint the underlying causes of mental disorders in women. They should take proactive measures to mitigate these causes, thereby decreasing the prevalence of anxiety, depression, and stress disorders through the implementation of effective interventions.